Dynamic drawing strategy identification related to handwriting behaviors in children [electronic resource] - Narges Tabatabaey Mashadi, 1979-, author 581003; Rubita Sudirman, supervisor 414128; Puspa Inayat Khalid, 1966- supervisor 515878; Fakulti Kejuruteraan Elektrik 540663 (2014)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2014